SELENIUM HETEROCYCLES XXXX [I] SYNTHESES OF 4- (2-PYRAZINYL) - 1, 2, 3: SELENADIAZOLE AND 4- (2-PYRAZILYL)' - l,2,3- THIADIAZOLE (Journal of Sciences, Islamic Republic of Iran)
Reaction of thionyl chloride with 2-acetyl-1- benzenesulfonylpyrrole semicarbazone (6 c) gave 4 - (1- benzenesulfonyl-2 - pyrrolyl) - 1, 2, 3 -thiadiazole (lc). Selenium dioxide oxidation of 2-acetylpyrazine semicarbazone (10) in acetic acid afforded 4- (2-pyrazinyl) - 1, 2, 3- selenadiazole (4). Reaction of thionyl chloride with compound 10 gave 4- (2-pyrazinyl) - 1, 2, 3- thiadiazole (3). Base catalized decomposition of 4 afforded the cis-fulvene 13. Similarly, reaction of 3 with a base gave the corresponding cis-fulvene 11. Heating compounds 11 or 13 gave respectively the corresponding trans isomers 12 or 14.